MANAGING LOCAL WISDOM IN ENGLISH TEACHING MATERIALS - Adzanil Prima Septy (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
The national system of education of Indonesia has emphasized on the importance of developing students’ competence and building characters according to the philosophy of national culture Pancasila. This also applies to English language teaching (ELT), that is, to develop a communicative competence while integrating ideal characters as good Indonesians. This argued that English language teaching should not simply let students copy foreign cultures in their communication learning, but importantly reflect an understanding to norms and values incorporating a sense of national integrity in their English proficiency, characterizing them as Indonesians in the global community.In spite of this, such ideal objective of ELT seems difficult to attain due to foreign-dependent learning resources that many English teachers often rely on. Besides, students’ learning success has often been indicated through their ability to express English in foreign ways to communicate leading them to disregard their local norms, values, and cultures. This paper will discuss an attempt to manage local wisdom content as learning resources in English teaching materials. The aim of such local wisdom content is to integrate students’ communicative competence with appropriate character development. In particular, this paper will suggest how teachers could manage English materials containing local wisdom to internalize appropriate understanding and characters, and how such materials could be organized into attractive ICT based media. This would be an attempt to ignite the brighter future of English teaching and learning in Indonesia multilingual society.